2006
DOI: 10.1091/mbc.e05-04-0375
|View full text |Cite
|
Sign up to set email alerts
|

The Slow Wallerian Degeneration Protein, WldS, Binds Directly to VCP/p97 and Partially Redistributes It within the Nucleus

Abstract: Slow Wallerian degeneration (Wld S ) mutant mice express a chimeric nuclear protein that protects sick or injured axons from degeneration. The C-terminal region, derived from NAD؉ synthesizing enzyme Nmnat1, is reported to confer neuroprotection in vitro. However, an additional role for the N-terminal 70 amino acids (N70), derived from multiubiquitination factor Ube4b, has not been excluded. In wild-type Ube4b, N70 is part of a sequence essential for ubiquitination activity but its role is not understood. We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 64 publications
4
73
2
Order By: Relevance
“…First, valosin-containing protein (VCP/p97) binds to the N-terminal 16 amino acids of Wld S and Ube4b. 30 Consequently, Wld S partially redistributes VCP into punctate intranuclear foci in some neuronal subtypes. Removing the N-terminal 16 amino acids of Wld S abolishes the targeting of VCP to intranuclear foci, and we confirm here that overexpressed Nmnat1 also fails to target VCP to intranuclear foci (Supplementary Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…First, valosin-containing protein (VCP/p97) binds to the N-terminal 16 amino acids of Wld S and Ube4b. 30 Consequently, Wld S partially redistributes VCP into punctate intranuclear foci in some neuronal subtypes. Removing the N-terminal 16 amino acids of Wld S abolishes the targeting of VCP to intranuclear foci, and we confirm here that overexpressed Nmnat1 also fails to target VCP to intranuclear foci (Supplementary Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Other data regarding the molecular mechanism of Wld S mediated axon protection suggest involvement of valosincontaining protein (VCP) that binds the N-terminal 16 aa of Wld S through a VCP binding motif (Laser et al, 2006). This region is necessary but not sufficient for axon protection in mice (Conforti et al, 2007) (Conforti, Wilbrey, Morreale, Janeckova, Beirowski, Adalbert, Mazzola, Di Stefano, Hartley, Babetto, Smith, Gilley, Billington, Genazzani, Ribchester, Magni, and Coleman, unpublished work) and is necessary for full strength phenotype in Drosophila (Avery, Sheehan, Kerr, Wang, and Freeman, unpublished work).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the previously identified Nmnat1 NLS (Sasaki et al, 2006) is also the main determinant of nuclear localization of full-length Wld S protein. We additionally identified a weak predicted NLS (PSORTII and NucPred predictions) within the N-terminal 16 aa of Wld S but chose not to mutate this region because its influence on Wld S biochemistry (Laser et al, 2006) could affect phenotype in other ways.…”
Section: Confocal Imaging and Fluorescence Intensity Quantificationmentioning
confidence: 99%
“…Interestingly, this study also showed that UFD2 interacted with calosin-containing protein (VCP), a member of the large family of AAA-type ATPases that are thought to possess chaperone activity, indicating that the mammalian UFD2a/VCP complex might function as an E3/chaperon complex in the response of neurons to stress. Recently, it has been reported the N70 of the Wlds protein bind to VCP directly, 87 indicating that the N70 might increase the expression level and protein stability of Wlds especially under stress conditions such as axonal injury. On the other hand, virus mediated in vitro overexpression may generate at high concentrations (1 to 20 mM) does not require any pretreatment, arguing against the need for nuclear effects.…”
Section: Wlds Vs Nmnat1: Stronger?mentioning
confidence: 99%